LITERATURE REVIEW : FAKTOR YANG MEMPENGARUHI KECEMASAN PADA MAHASISWA KEDOKTERAN - Verninda Dwi Saputri (Yayasan Pendidikan Medika Indonesia, 2024)
The challenges faced by students trigger mental health problems, one of which is anxiety. Anxiety is a feeling of excessive fear and anxious. Students generally feel learning anxiety, including medical students. This research aims to determine the factors of anxiety in medical students in various countries. The research method uses literature study or literature review. The literature review search used electronic databases including PubMed (pubmed.ncbi.nlm.nih.gov), Google Scholar (scholar.google.co.id), and Researchgate (www.researchgate.net). The search results obtained 10 selected articles from 10 countries for analysis after determining their suitability to the criteria. The research results are in the form of a summary including title, country, research purposes, method or measuring instrument, and research results in the form of factors related to anxiety in medical students from research in various countries. Based on research results and discussions, it can be concluded that the factors that influence anxiety in medical students in various countries include factors female students, age > 20 years, first level of study, heavy academic load, and poor social support.